Ethnic-specific relationships between haemostatic and oxidative stress markers in black and white South Africans: the SABPA study - Lammertyn, Leandi; Mels, Catharina M.C.; Pieters, Marlien; Schutte, Aletta E.; Schutte, Rudolph (Taylor & Francis, 2015)
Haemostatic- and oxidative stress markers are associated with increased cardiovascular risk. In the black population, evidence exists that both an imbalance in the haemostatic system and oxidative stress link with the development of hypertension. However, it is unclear whether these two risk components function independently or are related, specifically in the black population, who is known to have a high prevalence of stroke. We aimed to investigate associations between the haemostatic system and oxidative stress in black and white South Africans. We performed a cross-sectional study including 181 black (mean age, 44; 51.4% women) and 209 white (mean age, 45; 51.7% women) teachers. Several markers of the haemostatic- (von Willebrand factor, fibrinogen, plasminogen activator inhibitor-1, D-dimer and clot lysis time) and oxidant antioxidant (serum peroxides, total glutathione, glutathione peroxidase- and glutathione reductase activities) systems were measured. Along with a worsened cardiovascular profile, the black group had higher haemostatic-, inflammation- and oxidative stress markers as well as decreased glutathione peroxidase activity. In multiple regression analyses, fibrinogen was positively associated with serum peroxides (p<0.001) in both ethnic groups. In the black population, we found negative associations of von Willebrand factor and clot lysis time with glutathione peroxidase activity (p≤0.008), while a positive association existed between clot lysis time and serum peroxides (p=0.011) in the white population. We conclude that in the black population, decreased GPx activity accompanies an altered haemostatic profile, while in the white population associations may suggest that serum peroxides impair fibrin clot lysis.
Keywords: antioxidant capacity; cardiovascular; fibrinogen; gluthathione peroxidase; hydrogen peroxide